Molecular phylogeny and phylogeography of Holarctic species of Pluteus section Pluteus (Agaricales: Pluteaceae), with description of twelve new species - Justo, Alfredo; Malysheva, Ekaterina; Bulyonkova, Tatiana; Vellinga, Else C; Cobian, Gerry; Nguyen, Nhu; Minnis, Andrew M; Hibbett, David S (Phytotaxa, 2014)
The taxonomy and phylogeography of Pluteus section Pluteus in the Holarctic region was investigated using morphological and molecular data. Over 300 specimens spanning the major areas of boreal and temperate forests of the Northern Hemisphere were studied and nrITS and tef1 were obtained for phylogenetic analyses. In order to stabilize the taxonomy of the group all available type collections were studied and, if possible, sequenced. A total of 26 species occurring in Eurasia and North America were recovered in the phylogenetic analyses. Twelve species are described as new (Pluteus rangifer, P. elaphinus, P. hibbettii, P. eos, P. orestes, P. methvenii, P. shikae, P. kovalenkoi, P. leucoborealis, P. sepiicolor, P. oreibatus, P. atrofibrillosus), one is provisionally named (P. parilis) and one variety is raised to species rank (P. americanus). In many cases separation of the species based on morphology alone is challenging. In general, tef1 distinguishes the species better than nrITS. Structured infraspecific genetic variation was detected in the nrITS phylogenies for five species (P. atromarginatus, P. hibbettii, P. orestes, P. primus and P. shikae) and in the tef1 phylogenies for P. cervinus. Phylogeographic patterns are strikingly different among the species in this group and include widespread Holarctic species, exclusively Palearctic, putative disjuncts and endemics in each Holarctic subregion (Eastern/Western Palearctic and Nearctic). Identification keys are provided for each subregion.